PENGARUH INDEPENDENSI, KOMPETENSI, EXPECTATIONAUDITOR, KECERMATAN AUDITOR TERHADAP KUALITAS AUDIT PADA INSPEKTORAT DI PROVINSI KEPULAUAN RIAU - Efriyenti, Dian (EDUTECH CONSULTANT, 2018)
Abstract This study aims to test Independence, Competence, Expectation Auditor, Auditor's Accuracy to Audit Quality simultaneously and partially.The sample in this research is Inspectorate of Tanjungpinang City, Inspectorate of Regency of Bintan, And Inspectorate of Batam City. The type of data used is the primary data which is obtained data collected by the researchers in a direct way from the source. Data were collected by using questionnaires distributed directly to respondents. The analysis method used is multiple linear regression model. To test the hypothesis simultaneously and partially used F Test and Test T. The result of hypothesis test and test show that simultaneously variable of Independence, Competence, Expectation Auditor, Auditor's Dignity has Influence on Audit Quality. Partially Independence, Expectation Auditor, and Auditor's Accuracy does not have an effect on Audit Quality, while Competence Affects Quality of Audit.